2022
DOI: 10.3390/pharmaceutics14112485
|View full text |Cite
|
Sign up to set email alerts
|

DNAJB6-Containing Extracellular Vesicles as Chaperone Delivery Systems: A Proteomic Analysis

Abstract: Cell-derived extracellular vesicles (EVs) are effectors of cell-to-cell communication that are in the spotlight as promising candidates for in vivo drug delivery because of their ability to enter cells and deliver cargo. For example, proteins of interest can be loaded into EVs to mediate protein transfer into target cells. To determine causality between EV content and function, which is also important to assess the clinical safety of EVs, it is crucial to comprehensively characterize their complete molecular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…After protein co-expression network analysis in human brain-derived EVs, they found EVs derived from astrocytes are the most significant enrichment module and highlighted the potential pathogenesis mechanism in AD. Additionally, promising and novel AD biomarkers of EVs derived from various sources were discovered [ 61 , 62 , 63 , 64 , 65 , 66 , 67 ], and researchers compared the proteomic landscape following the knockout or overexpression of important genes to understand AD pathology [ 68 , 69 ]. Jewett et al [ 70 ] revealed the dysregulated protein of EVs isolated from the Gba1b mutant (GBA deficiency) Drosophila model to promote abnormal protein aggregation in neurons of PD.…”
Section: An Overview Of the Ev Biology In Disease Contextmentioning
confidence: 99%
“…After protein co-expression network analysis in human brain-derived EVs, they found EVs derived from astrocytes are the most significant enrichment module and highlighted the potential pathogenesis mechanism in AD. Additionally, promising and novel AD biomarkers of EVs derived from various sources were discovered [ 61 , 62 , 63 , 64 , 65 , 66 , 67 ], and researchers compared the proteomic landscape following the knockout or overexpression of important genes to understand AD pathology [ 68 , 69 ]. Jewett et al [ 70 ] revealed the dysregulated protein of EVs isolated from the Gba1b mutant (GBA deficiency) Drosophila model to promote abnormal protein aggregation in neurons of PD.…”
Section: An Overview Of the Ev Biology In Disease Contextmentioning
confidence: 99%